Fowl cholera vaccine production: process optimization in laboratory scale fermenter - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Yob, Nor Jannah; Samsury, Intan Zahrah; Syed Hassan, Sharifah; Ngah Hamid, Akma (IIUM Press, 2011)

(untitled)
The process optimization of Pasteurella multocida fermentation for fowl cholera vaccine production in 2L laboratory scale fermenter was successfully carried out in stirred tank reactor (STR). This study focuses on the maximizing the cell growth and protein production of P. multocida by optimizing process of various fermentation condition. The process optimization was designed for different level of parameters that were dissolved oxygen concentration (pO2), stirred speed (rpm)and pH using Taguchi's Experimental Robust Design by STATISTICA 6.0 agitation (200 rpm) and for antigen protein production was significantly affected by higher level (1 vvm). The correlation between the parameters was very affecting the productivity of the vaccine produced.